Closing the Gap: Territorial Cohesion through Polycentric Development - Evert Meijers; Bas Waterhout; Wil Zonneveld (European Journal of Spatial Development)
This article discusses and analyses national polycentric development policies aiming at cohesion. Due to its insertion in the 1999 European Spatial Development Perspective ‘polycentricity’ has become an important concept in discussions on Europe’s territorial and economic development. Its content remains however rather unclear. This paper contributes to the discussion on the meaning of polycentricity by looking at national polycentric development policies. These policies can be distinguished according to two types of disparities, or gaps, which they try to bridge. The first concerns the gap between different levels of the national urban hierarchy, the most common being the gap between a primate capital city and the next category of cities. The second gap is the one between cities located in regions with diverging rates of socio-economic development. On the basis of a conceptual and quantitative discussion of these gaps a basic definition is presented of what polycentric development policies are about: policies that address the distribution of economic and/or economically relevant functions over the urban system in such a way that the urban hierarchy is flattened in a territorially balanced way. A discussion of the polycentric development policies of France, Poland and Germany illustrates our findings. The article concludes that for the period 2007-2013 – the new EU budget period – a clear synergy is needed between EU and national policies and that without such synergy policies cannot be effective.